Immersed tunnel techniques proceedings of the conference organized by the Institution of Civil Engineers and held in Manchester on 11-13 April 1989. (Thomas Telford, 1990)
Drawing together a range of international experience in the techniques of planning, design and construction of submerged tubes, this book looks at the many uses of these tunnels - outside their principal application for rail or vehicular traffic - such as services, effluent outfalls, etc.